Sexual and Reproductive Health: Knowledge, Attitude, and Perceptions among Young Unmarried Male Residents of Delhi - Jitendra Kumar Meena; Anjana Verma; Jugal Kishore; Gopal Krishan Ingle (Hindawi Limited, 2015)
Context. Men play a significant role in all spheres of domestic life including reproduction. Youth is a period of critical development and ignoring sexual and reproductive health (SRH) needs of young men ought to have wider social and health consequences. Aims and Objectives. To assess the knowledge, attitude, and perceptions regarding SRH among young unmarried men (18-25 years). Settings and Design. A semiqualitative study conducted across four health centers (2 rural, 2 urban) across Delhi. Materials and Methods. Focus group discussions (FGDs) were held among sixty-four participants regarding various aspects of SRH. Data Analysis. The data generated were analyzed using free listing and thematic content analysis along with simple quantitative proportions for different variable groups. Results. Good knowledge regarding HIV/AIDS was observed though found poor regarding other STIs/RTIs. Inadequate knowledge and negative attitude towards SRH and condom use were observed among rural participants. Peer group and mass media were the commonest SRH information sources among rural and urban participants, respectively. Conclusions. Poor SRH knowledge, perceptions, and available nonformal, unreliable information sources expose young men to poor SRH outcomes. Early, comprehensive SRH information provision can have life-long protective benefits to them and their partners.